Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/acel.12306
|View full text |Cite
|
Sign up to set email alerts
|

Aging and radiation: bad companions

Abstract: Aging involves a deterioration of cell functions and changes that may predispose the cell to undergo an oncogenic transformation. The carcinogenic risks following radiation exposure rise with age among adults. Increasing inflammatory response, loss of oxidant/antioxidant equilibrium, ongoing telomere attrition, decline in the DNA damage response efficiency, and deleterious nuclear organization are age-related cellular changes that trigger a serious threat to genomic integrity. In this review, we discuss the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 93 publications
1
42
1
1
Order By: Relevance
“…In our study, the majority of hematological cancer cases have been observed among patients aged 60 years and over (40.4 % of MH). This result is predictable since cancer is triggered after several genetic mutations that accumulate with age [ 34 , 35 ]. In this age group, there was a female predominance with a male to female ratio of 0.9.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the majority of hematological cancer cases have been observed among patients aged 60 years and over (40.4 % of MH). This result is predictable since cancer is triggered after several genetic mutations that accumulate with age [ 34 , 35 ]. In this age group, there was a female predominance with a male to female ratio of 0.9.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relative risk of cardiovascular events was reported up to 60-fold higher in childhood cancer survivors that received a higher cardiac mean dose of >30 Gy compared to patients who received either no RT or a dose to the heart of 0.1 Gy or less [158]. While some studies report exposure at an older age may also be a risk factor for more severe normal tissue toxicity [159,160], a rodent study reported increased mortality rates and incidence of RT pneumonitis compared to geriatric rats after 13 Gy partial body irradiation [161]. Therefore, in preclinical research it is important to treat animals at an age that is most appropriate for the clinical scenario that is under investigation, which may also be dependent upon the sex and strain of the animal.…”
Section: Preclinical Models To Study Cardiac Radiation Toxicities: Anmentioning
confidence: 99%
“…High levels of cf-DNA in the urine of aged rats subjected to IR is obviously associated with the presence of defective cells (damaged organelles and DNA) having low activity of reparation systems in the tissues of these rats prior to irradiation. 24 It should be noted that due to the reduction of activity in the functioning of protective and reparative systems, higher DNA damage and cell death rates can be observed in the kidneys, similarly to other tissues of aged animals, as compared to young animals. 25 It can also be assumed that elevation of cf-DNA level in the urine of irradiated rats is likely contributed by the development of radiation-induced nephropathy in these animals.…”
Section: Discussionmentioning
confidence: 99%